Eficácia do uso de stents na dacriocistorrinostomia endoscópica: metanálise - Orsolini, Maria Julia de Barros [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
Objective: To determine if stents increase the success rate of endoscopic dacryocystorhinostomy (DCR-EN) Method: Systematic review of randomized clinical trials of DCR-EN, comparing surgeries performed with and without stents in children older than 10 years of age and adult patients, with primary lacrimo-nasal duct (LND) obstruction. The outcomes were LND patency and adverse events (complications). We searched the databases of Web of Science, Scopus, Embase, Cochrane, PubMed, Lilacs until May 2018. The RevMan 5.3 software provided by the Cochrane Collaboration was used for meta-analysis. Results: Ten studies involving 887 surgeries were included. Five studies were conducted in India, and each of the others were conducted in Canada, Turkey, Saudi Arabia, China and Finland. Lacrimo-nasal duct patency meta-analysis showed stents did not interfere in the chance of success in relation to non-use of the stents to obtain lacrimal viability (OR 1.62, 95% CI 1.00 to 2.64, I2 = 0%). It was not possible to perform a meta-analysis regarding the adverse effects and a descriptive analysis was made of the general complications and complications due to the stents. Conclusion: The use or no of stents in DCR-EN probably does not make any difference in the NLD patency. Further studies may better define whether there is a trend toward a better success rate with the use of stent. Key words: dacryocystorhinotomy, endoscopic, stent, success, meta-analysis

Objetivo: Definir se o uso de stents aumenta a taxa de sucesso da dacriocistorrinostomia endoscópica (DCR-EN). Método: Revisão sistemática de ensaios clínicos randomizados referentes a DCR-EN, comparando as cirurgias realizadas com e sem uso de stents em crianças acima dos 10 anos de idade e adultos, com obstrução adquirida do ducto lacrimo-nasal (DLN). Os desfechos avaliados foram a patência do DLN e os eventos adversos (complicações). Foram pesquisadas as bases de dados: Web of Science, Scopus, Embase, Cochrane, PubMed, Lilacs até maio de 2018. Utilizou-se para metanálise o software RevMan 5.3 fornecido pela Colaboração Cochrane. Resultados: Dez estudos envolvendo 887 cirurgias foram incluidos. Cinco estudos foram realizados na India, um em cada um dos países a seguir: Canada, Turquia, Arabia Saudita, China e Finlândia. A metanálise da patência do DLN mostrou que os stents não interferiram na chance de sucesso em relação ao não uso dos stents para a obtenção de permeabilidade da via lacrimal (OR 1,62, IC 95% 1.00 a 2.64; I2 = 0%). Quanto aos efeitos adversos não foi possível realizar metanálise, tendo sido feita análise descritiva das complicações gerais e complicações dos stents. Conclusão: O uso ou não de stents na DCR-EN provavelmente faz pouca ou nenhuma diferença na patência do DLN. Novos estudos poderão melhor definir se há tendência de melhor taxa de sucesso com o uso de stents.
Efficacy of stents in endoscopic dacryocystorhinostomy surgery: meta analysis
Keywords: Dacriocistorrinostomia; Endoscopia; stent; Sucesso; Metanálise; dacryocystorhinotomy; endoscopic; success; meta-analysis